The making of curriculum : collected essays - Goodson, Ivor. (Washington, DC ; London : Falmer Press, 1995)
"This is the second edition of a book first published in 1988 in which Ivor Goodson explores a number of aspects of the 'invention' and promotion of the so-called traditional subjects. He describes the way the subjects develop over time to a point where they can be presented and promoted as 'academic' disciplines. He shows that the claim to be academic is in fact the result of a substantial political contest covering a century or more. The traditional subject is, in short, invented. Once we look at the political process of inventing, promoting and sustaining the school subject a very different perspective to that conventionally employed for understanding the school curriculum emerges. The 'traditional subjects' turn out to be a kind of politician's 'Piltdown man' and, once this is grasped, the existing discourse over the secondary school curriculum is seen in a very different light. By furthering our understanding of the history and politics of curriculum, this book provides a series of challenging insights for those concerned to make sense over the current debate over schooling. The second edition is brought up to date by Goodson considering the impact of the National Curriculum, and by Bill Pinar writing an introduction which places Goodson's work in a North American context."--Jacket
Part I The Search for Sources -- chapter 1 Investigating State Schooling: The Search for Sources -- chapter 2 Studying Curriculum -- chapter 3 Etymologies, Epistemologies and The Emergence of Curriculum: A Speculative Essay -- part II The Search for Methods -- chapter 4 History of Education in England: Conflicting Paradigms -- chapter 5 Investigating State Schooling: Exploring New Methods -- part III Essays and Exemplars -- chapter 6 Teachers' Life Histories and Studies of Curriculum and Schooling -- chapter 7 History, Context and Qualitative Methods -- chapter 8 Defining a Subject for the Comprehensive School -- chapter 9 The Micropolitics of Curricula Change: European Studies -- chapter 10 Becoming a School Subject -- chapter 11 The Making of Curriculum -- chapter 12 Conclusions, Complexities and Contemporary Initiatives in the Making of Curriculum: Towards a National Curriculum.
Includes bibliographical references (pages 207-215) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Education, Secondary -- Curricula -- History; Curriculum planning -- History; Curriculum change -- History; Enseignement secondaire -- Programmes d'études -- Histoire; Programmes d'études -- Changements -- Histoire; EDUCATION -- Secondary; Curriculum change; Curriculum planning; Education, Secondary -- Curricula; Secondary schools -- Curriculum -- History; Great Britain; Electronic books; History